PENGARUH MEDIA AUDIO VISUAL TERHADAP MOTIVASI BELAJAR SISWA DALAM MATERI SEPAK BOLA DI KECAMATAN CIKAUM - Naelul Fadly; Dermawan, Dikdik Fauzi; Effendi, Rustam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using audiovisual media on students' learning motivation in soccer material in Cikaum District. The background of this research is based on the low level of students' learning motivation in physical education due to monotonous teaching methods, which lead to boredom. Therefore, innovation in learning is needed, one of which is through the use of audiovisual media. This study employed a quantitative approach with an experimental method. The research design used was a one-group pretest-posttest design. The population of this study consisted of 10th-grade TBSM students from several schools in Cikaum District, with a sample of 55 students selected using simple random sampling technique. The research instrument was a learning motivation questionnaire administered before and after the treatment. Data were analyzed using normality test, homogeneity test, and hypothesis testing (paired sample t-test) with the help of SPSS software. The results of the study indicate that there is a significant effect of using audiovisual media on students' learning motivation in soccer material. This is evidenced by an increase in students' motivation scores after being given treatment using audiovisual media. Thus, audiovisual media can be an effective alternative to enhance students' learning motivation in physical education, especially in soccer material.